Typification of some Oncocyclus (Iris, Iridaceae) names related to the Turkish flora - Boltenkov, Eugeny V.; Güner, Adi̇l (Phytotaxa, 2020)
In view of the forthcoming treatment of Turkish irises for Resimli Türkiye Florasi (The Illustrated Flora of Turkey), twenty names belonging to Iris sect. Oncocyclus are typified, or nomenclatural notes provided. Lectotypes are designated here for I. chrysantha, I. maculata, I. manissadjianii, I. medwedewii, I. paradoxa var. choschab, and I. sprengeri. A second-step lectotypification for I. heylandiana is provided. Neotypes for the names I. elisabethae, I. gatesii, I. lupina, I. polakii, I. speciosissima, and I. urmiensis are designated. Epitypes for the names I. maculata, I. paradoxa var. choschab, I. sprengeri, and I. sari are designated. For the previously typified names, the lectotypes of I. barnumiae, I. elegantissima, I. iberica, I. lycotis and I. paradoxa, and the holotypes of I. kirkwoodiae and I. sari, are indicated. Authorships of the names for I. iberica and I. urmiensis are corrected.